Editorial - Yuktanandana, MD, Pongsak (Journal of Southeast Asian Orthopaedics, 2022)
The current editorial board of the Royal College of Orthopaedic Surgeons of Thailand (RCOST) has been working since May, 2013. One of our main policy is to improve our journal to the national level (cited in Thai Journal Citation Index (TCI)) and to international level (cited in international database of Scopus and PubMed). The Thai Journal of Orthopaedic Surgery is an official journal of RCOST. TCI has started accredited all Thai scientific journals and classified them into three categories. The first category is the journals that have been approved by TCI and and are listed in the TCI database. The second category is the journals that are in the reaccreditation process but are currently listed in the TCI database. The last category includes the journals which quality does not reach the TCI requirement and yet listed in the TCI database. We are successfully put The Thai Journal of Orthopaedic Surgery into the Thai Journal Citation Index (TCI) as the second category journal. The quality of The Thai Journal of Orthopaedic Surgery is improving and we plan to resubmit our data in order to be approved as the first category journal. As the Thai Journal of Orthopaedic Surgery is currently listed in the second category, TCI allows journals in the second and the third categories to be improved and resubmitted their data every three years. In this volume, there are four research articles, published: Intraarticular Tranexamic Acid Decreased Transfusion Rates and Blood Loss in Primary Total Hip Arthroplasty: A Prospective Randomized Double-Blind Placebo-Controlled Trial Gentamicin Release from Bone Cement: A Comparative Study between Hand Made Liquid & Powder Gentamicin beads Cost Analysis of Blood Transfusion and Tranexamic acid in Primary Total Knee Arthroplasty Metastasis of cardiac rhabdomyosarcoma at lumbar spine: case report Once again, we hope that we will receive sufficient high quality articles to obtain a good ranking. In the upcoming volume, which will be distributed in the Royal College of Orthopaedic Surgeons of Thailand and ASEAN Orthopaedic Association (RCOST & AOA) combined meeting during October 6-8, 2016, we assure that more original articles, review articles, and case reports will be included. Lastly, we would like to express our sincere gratitude to all authors, all members of the editorial board, all peer reviewers and editorial office staffs. They all work very hard to improve a high quality and standard for the journal.